Microstructure, Mechanical and Superelastic Properties of Ti-Zr-Nb Alloy for Biomedical Application Subjected to Equal Channel Angular Pressing and Annealing - Vadim Sheremetyev; Mikhail Derkach; Anna Churakova; Aleksander Komissarov; Dmitry Gunderov; Georgy Raab; Vladimir Cheverikin; Sergey Prokoshkin; Vladimir Brailovski (Metals, 2022)
Biomedical Ti-18Zr-15Nb (at.%) shape memory alloy was subjected to a low-temperature equal channel angular pressing (ECAP) at 200 °C for three passes and post-deformation annealing (PDA) in the 400–650 °C temperature range for 1 to 60 min. It was observed that ECAP led to the formation of an inhomogeneous highly dislocated substructure of β-phase with a large number of differently oriented deformation bands containing nanograined and nano-subgrained areas. In this state, the alloy strength increased significantly, as compared to the undeformed state, but its ductility and superelasticity deteriorated appreciably. As a result of a short-term (5 min) PDA at 550–600 °C, the processes of polygonization of an entire volume of the material and recrystallization inside the deformation bands were observed. After PDA at 600 °C for 5 min, the alloy manifested a relatively high strength (UTS = 650 MPa), a satisfactory ductility (δ = 15%) and a superior superelastic behavior with a maximum superelastic recovery strain of εrsemax = 3.4%.